2005
DOI: 10.1152/jn.00548.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillation Maintains Stimulus Structure-Dependent Synchronization in Cat Visual Cortex

Abstract: Samonds, Jason M. and A. B. Bonds. Gamma oscillation maintains stimulus structure-dependent synchronization in cat visual cortex. J Neurophysiol 93: [223][224][225][226][227][228][229][230][231][232][233][234][235][236] 2005. First published July 28, 2004; doi:10.1152/jn.00548.2004. Visual cortical cells demonstrate both oscillation and synchronization, although the underlying causes and functional significance of these behaviors remain uncertain. We simultaneously recorded single-unit activity with microelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 75 publications
8
88
0
Order By: Relevance
“…Although there appears to be an increase in the number of spikes occurring at the start and end of each movie frame, the increase at the start of the movie frame in all likelihood is the continuation of the increase at the end of the preceding movie frame. This perhaps reflects the fact that these cells have response latencies between 33 and 40 ms, which is consistent with other studies of response latencies in the primary visual cortex of the anesthetized cat (Samonds and Bonds, 2005).…”
Section: Interspike Interval Distributionssupporting
confidence: 91%
“…Although there appears to be an increase in the number of spikes occurring at the start and end of each movie frame, the increase at the start of the movie frame in all likelihood is the continuation of the increase at the end of the preceding movie frame. This perhaps reflects the fact that these cells have response latencies between 33 and 40 ms, which is consistent with other studies of response latencies in the primary visual cortex of the anesthetized cat (Samonds and Bonds, 2005).…”
Section: Interspike Interval Distributionssupporting
confidence: 91%
“…Snider et al (1998) found that monosynaptic connections (CCGs with peaks offset from zero) between neurons in cat V1 were more sensitive to stimulus orientation than contrast. Samonds and Bonds (2004) showed that common-input CCGs are larger for effectively oriented stimuli. Llampl et al (1999) showed that membrane potential fluctuations between pairs of V1 neurons are correlated and stimulus dependent, also consistent with our data.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…However, most studies investigating synchrony between single V1 cortical neurons have focused either on the effect of altering the "gestalt" characteristics of the stimulus (Livingstone, 1996) or have used indirect measurements such as the synchrony of multiunit activity (MUA) (Lamme and Spekreijse, 1998) or the strength of oscillations in single-unit activity, MUA, or the local field potential (LFP) (Gray et al, 1989; synchrony, this is because different stimuli might recruit different subpopulations of neurons in the recorded signal. For measures of oscillatory firing, this is because the stimulus dependence of oscillations is controversial (Ghose and Freeman, 1992;Young et al, 1992) and because some studies have failed to find a strong relationship between oscillatory firing and synchronous firing of single neurons (Samonds and Bonds, 2004) (but see Maldonado et al, 2000). To compare the sensitivity of spike count and spike timing correlation between single V1 neurons, we therefore investigated the orientation dependence of synchrony in our population of pairs.…”
Section: Orientation Dependence Of Spike Timing Correlationmentioning
confidence: 99%
“…Recordings in monkey have also shown that visual gamma oscillations are modulated by orientation (Friedman-Hill et al, 2000) and show sharper orientation tuning than lower frequency oscillations (Frien et al, 2000). Given that behavioral orientation discrimination thresholds are better than might be predicted from individual neuronal receptive fields, it has been proposed that visual gamma oscillations may also provide a mechanism for synchronizing neurons into a cooperative neural assembly that then enhances orientation discrimination performance (Samonds et al, 2004;Samonds and Bonds, 2005).…”
Section: Introductionmentioning
confidence: 99%